School children’s mental health during the COVID-19 pandemic - Martinsen, Kristin; Lisøy, Carina; Wentzel-Larsen, Tore; Neumer, Simon-Peter; Rasmussen, Lene-Mari Potulski; Adolfsen, Frode; Sund, Anne Mari; Ingul, Jo Magne (Frontiers in Psychology, 2024)
Introduction The COVID-19 pandemic significantly impacted the daily routines of children, with social distancing and quarantine leading to reduced social interactions and potential increased conflicts within families. These factors can increase the risk for anxiety and depression while reducing overall quality of life. Methods Our study included 1843 school children aged 8 to 12 from 56 schools over a 2.5-year period before and during the pandemic. This multi-wave cross-sectional study utilized baseline data from an optimization trial of an indicated preventive intervention. The main outcomes were self-reported symptoms of anxiety and depression, and quality of life was the secondary outcome measure. Furthermore, responses to COVID-relevant questions were measured using a self-composed scale. Our objectives were to compare anxiety and depression symptom levels between cohorts of children who participated in the study before and during the pandemic, to examine if anxiety or depression predicted the COVID response, and whether anxiety and depression and subtypes of anxiety had an impact on quality of life during the pandemic. Linear regression and interaction models were used to examine relevant associations. Results Levels of anxiety and depression were higher in all waves compared to pre-pandemic levels. Quality of life was lower during the pandemic than before the pandemic, particularly among children with generalized anxiety symptoms. Quality of life was negatively associated with loneliness. Discussion Our study revealed that children reported higher anxious and depressive symptoms during the pandemic compared to pre-pandemic levels, as well as reduced quality of life. Lockdowns and restrictions may have contributed to this burden. Additionally, self-reported loneliness was a significant possible consequence of the restrictive measures imposed on children during the pandemic. Additional research is needed to investigate the long-term effects of the pandemic on children, particularly regarding the stability of elevated levels of anxiety and depression. Such studies could examine whether these conditions are indicative of a trajectory toward more severe internalizing disorders. Clinical trial registration: NCT04263558.